Immunomodulation Potential of Probiotics: A Novel Strategy for Improving Livestock Health, Immunity, and Productivity - A. K. M. Humayun Kober; Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; Julio Villena; Haruki Kitazawa (Microorganisms, 2022)
Over the past decade, the use of probiotics as feed supplements in animal production has increased considerably due to the ban on antibiotic growth promoters in livestock. This review provides an overview of the current situation, limitation, and prospects for probiotic formulations applied to livestock. Recently, the use of probiotics in livestock has been suggested to significantly improve their health, immunity, growth performance, nutritional digestibility, and intestinal microbial balance. Furthermore, it was reported that the use of probiotics in animals was helpful in equilibrating their beneficial microbial population and microbial turnover via stimulating the host immune response through specific secretions and competitive exclusion of potentially pathogenic bacteria in the digestive tract. Recently, there has been great interest in the understanding of probiotics targeted diet and its ability to compete with harmful microbes and acquire their niches. Therefore, the present review explores the most commonly used probiotic formulations in livestock feed and their effect on animal health. In summary, this article provides an in-depth knowledge about the formulation of probiotics as a step toward a better alternative to antibiotic healthy growth strategies.